Cartofonias: expedições ao território volátil dos sons - Martins, Guilherme de Castro Duarte (2010)
The following work aims to investigate the presence of sound on contemporary visual arts, through the study of artworks from artists who make use of the sonic matter to change and make arise new time-spaces in the middle of the daily experience. I investigate mainly the works of the Scotish artist Susan Philipsz (Lowlands, 2010) and the Brazilian artist Raquel Stolf (Grilo, 2006). I start from coining the concept of cartophonies, that would mean sound maps resulting from the cross-over of noises emitted not only from the artworks I study, but originated also from its surroundings, composing puzzles audible and inaudible forces, that circulate around and through these works. As sound maps in constant mutation, the concept of cartophony was produced as a mobile tool for the present research, helping to understand how sound not only represents the space it traverses, but also participates on the creation of the volatile lines of this space, modifying it and being modified by it every second.